2013
DOI: 10.1371/journal.pone.0056454
|View full text |Cite
|
Sign up to set email alerts
|

Decision Rules and Group Rationality: Cognitive Gain or Standstill?

Abstract: Recent research in group cognition points towards the existence of collective cognitive competencies that transcend individual group members’ cognitive competencies. Since rationality is a key cognitive competence for group decision making, and group cognition emerges from the coordination of individual cognition during social interactions, this study tests the extent to which collaborative and consultative decision rules impact the emergence of group rationality. Using a set of decision tasks adapted from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 31 publications
3
60
1
Order By: Relevance
“…Based on these tasks we evaluated individual rationality at time 2 (IRT2). This procedure fits group synergy research (Larson, 2007; Curşeu et al, 2013, 2014; Meslec and Curşeu, 2013) as it allows for computing weak and strong group synergy. It also aligns well with the procedures used in group-to-individual transfer of learning research (Schultze et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these tasks we evaluated individual rationality at time 2 (IRT2). This procedure fits group synergy research (Larson, 2007; Curşeu et al, 2013, 2014; Meslec and Curşeu, 2013) as it allows for computing weak and strong group synergy. It also aligns well with the procedures used in group-to-individual transfer of learning research (Schultze et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…The group synergy framework has been used to describe the emergence of group rationality as a collective decision-making competence (Curşeu et al, 2013, 2014; Meslec and Curşeu, 2013). Groups that achieve weak synergy are those groups that collectively are more rational than the average rationality of their individual members, while groups that achieve strong synergy are those groups that collectively are more rational than their most rational group member.…”
Section: Group-to-individual (G-i) Transfer Of Learningmentioning
confidence: 99%
“…Team literature shows that a decentralised structure facilitates collaboration (Sparrowe et al, 2001). Also for decision making in teams it has been shown that such a collaborative structure is beneficial 11 (Curseu et al, 2013). A decentralised structure might reduce the negative effects resulting from diversity, because problems related to misunderstanding each other might be reduced.…”
Section: ) Project Governance: Project Structure and Project Managementmentioning
confidence: 99%
“…High and low intergroup competition consultative groups (groups in which the leader decides upon consultation) shows that collaborative groups perform better (Campion et al, 1996) and make more rational collective choice (Curseu et al, 2013) than consultative groups.…”
mentioning
confidence: 99%